Design and implementation of an aqua rover to collect surface trash - Hossain, Md. Jobaar; Bhattacharjee, Bipro; Paik, Swapnil; Otondrilla, Sanjida Haque (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.